Pre-doped sheet for power storage device and method for producing same
A pre-doping sheet with a lithium metal composite oxide having a reverse fluffy structure and specific Li/Me ratios effectively addresses the challenge of maintaining electrode strength and achieving high rate performance in power storage devices, enhancing the efficiency of lithium ion distribution without the need for pre-doping agents.
Patent Information
- Application Number
- JP2021558217
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-11-19
- Filing Date
- 2020-10-13
- Publication Date
- 2025-02-03
- Estimated Expiration
- 2040-10-13
AI Technical Summary
Existing methods for pre-doping lithium ions in power storage devices, such as lithium-ion batteries and capacitors, face challenges in maintaining electrode strength while achieving high rate performance due to the use of metal lithium foil and lithium titanate compounds, which increase manufacturing costs and reduce volume energy density.
A pre-doping sheet containing a lithium metal composite oxide with a reverse fluffy structure and specific molar ratios of lithium to metal elements (Li/Me) is used, eliminating the need for pre-doping agents and ensuring effective pre-doping without compromising electrode strength.
The solution provides a power storage device with excellent rate performance and maintains electrode strength, overcoming the limitations of previous methods by ensuring uniform ion distribution and reducing the formation of pre-doping pills.
Smart Images

Figure 0007625533000005 
Figure 0007625533000001 
Figure 0007625533000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a pre-doped sheet used in electricity storage devices such as lithium ion batteries, lithium ion capacitors, and electric double layer capacitors. [Background technology]
[0002] It is known that in power storage devices such as lithium ion batteries, lithium ion capacitors, and electric double layer capacitors, the volumetric energy density of the power storage device can be increased by pre-doping the negative electrode with lithium ions to lower the potential of the negative electrode. In recent years, a method has been proposed in which a metal foil having a plurality of through holes is used as a current collector, and a metal lithium foil is placed in an electrode in which a large number of positive and negative electrodes are stacked, thereby pre-doping the negative electrode with lithium ions via an electrolyte.
[0003] Patent Document 1 describes an electric storage device having an electrode including an electrode current collector having a plurality of through holes and an electrode mixture layer provided on the electrode current collector, and an ion supply source connected to the electrode current collector and supplying ions to the electrode mixture layer, the electrode current collector being provided with a first region having a predetermined through hole aperture ratio and a second region having a through hole aperture ratio larger than that of the first region, the first region being an edge portion of the electrode current collector, and the second region being a central portion of the electrode current collector. The device also describes that a lithium electrode is incorporated in the electric storage device, the lithium electrode has a lithium electrode current collector to which a metallic lithium foil as an ion supply source is pressed, and that lithium ions are pre-doped from the lithium electrode to the negative electrode by injecting an electrolyte. According to this, it is said that the penetration state of the electrolyte can be adjusted, and ions can be uniformly doped into the electrode. However, the pre-doping method described in Patent Document 1 has a problem that the manufacturing cost is high because a metallic foil having a plurality of through holes and a metallic lithium foil are used in the current collector, and further, the volume energy density of the electric storage device is reduced.
[0004] On the other hand, a pre-doping method that does not use metallic lithium foil has also been proposed. For example, Patent Document 2 discloses a method for pre-doping Li a TiO b A pre-doping agent for lithium ion capacitors is described, characterized in that the main component is a compound represented by (1.5≦a≦4.5, 2.7≦b≦4.8). According to this, since the main component is lithium titanate having a specific composition, lithium ions necessary for pre-doping can be generated by normal charging operation (aging), and pre-doping can be performed without using a metal lithium foil as in the past. However, the pre-doping agent described in Patent Document 2 is based on the premise that it is mixed with a positive electrode material, and such a pre-doping method has the problem that the strength of the positive electrode decreases, the film thickness of the positive electrode increases, the resistance increases, and the performance of the storage device decreases. In addition, Patent Document 2 does not describe or suggest that a lithium metal composite oxide in which the molar ratio Li / Me of a specific metal element (Me) and lithium metal satisfies a specific range, the lithium metal composite oxide has an inverse fluorite structure, and the content of the pre-doping agent containing the lithium metal composite oxide satisfies a specific range, and a pre-doping method that can provide a storage device with excellent rate performance while maintaining electrode strength has been desired. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 5220510 [Patent Document 2] JP 2019-87590 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention has been made to solve the above problems, and can effectively perform pre-doping without blending a pre-doping agent into an electrode, and is suitable for use as a power storage device having excellent rate performance while maintaining electrode strength. An object of the present invention is to provide a pre-doping sheet for a power storage device containing a lithium metal composite oxide having an inverse fluorite structure.
Means for Solving the Problems
[0007] The above problems are solved by providing a pre-doping sheet for a power storage device containing a pre-doping agent containing a lithium metal composite oxide, wherein the lithium metal composite oxide contains lithium (Li) and at least one metal element (Me) selected from the group consisting of Fe, Al, Mn, and Co, the lithium metal composite oxide has an inverse fluorite structure, the Li / Me (molar ratio) in the lithium metal composite oxide satisfies 3.0 < Li / Me ≦ 7.5, and the content (X) of the pre-doping agent satisfies 0.3 < X < 6.0 mg / cm 2 This is solved by providing a pre-doping sheet for a power storage device characterized by satisfying the above.
[0008] At this time, in X-ray diffraction measurement, it is preferable that the lithium metal composite oxide has diffraction peak intensities at 2θ (diffraction angle) = 23.7 ± 0.5°, 33.6 ± 0.7°, 36.5 ± 0.7°, and 56.7 ± 0.5°.
[0009] A separator for a power storage device including the pre-doping sheet is a preferred embodiment, and a power storage device including the pre-doping sheet is also a preferred embodiment.
[0010] The above problems are also solved by providing a method for manufacturing a pre-doping sheet for a power storage device containing a pre-doping agent containing a lithium metal composite oxide, the method being characterized by coating a paint containing the pre-doping agent and an organic solvent on the surface of a porous sheet substrate.
[0011] The above problem is also solved by providing a method for manufacturing a pre-doped sheet for a power storage device including a pre-doping agent containing a lithium metal composite oxide, the method being characterized by kneading and molding the pre-doping agent in a resin.
[0012] The above problem is also solved by providing a method for manufacturing a pre-doped sheet for a power storage device including a pre-doping agent containing a lithium metal composite oxide, the method being characterized by applying a coating material containing the pre-doping agent and an organic solvent to the surface of a release film substrate.
Advantages of the Invention
[0013] According to the present invention, a pre-doped sheet for a power storage device containing a lithium metal composite oxide having an inverse fluorite structure can be provided. By using the pre-doped sheet of the present invention, pre-doping can be effectively performed without blending a pre-doping agent into the electrode, so that a power storage device excellent in rate performance while maintaining electrode strength is preferably provided.
Brief Description of the Drawings
[0014] [Figure 1] It is a diagram showing a state of a 90° bending test in an example.
Embodiments for Carrying Out the Invention
[0015] The pre-doped sheet for a power storage device of the present invention (hereinafter, may be abbreviated as "pre-doped sheet") contains a pre-doping agent containing a lithium metal composite oxide, the lithium metal composite oxide contains lithium (Li) and at least one metal element (Me) selected from the group consisting of Fe, Al, Mn, and Co, the lithium metal composite oxide has an inverse fluorite structure, Li / Me (molar ratio) in the lithium metal composite oxide satisfies 3.0 < Li / Me ≦ 7.5, and the content (X) of the pre-doping agent satisfies 0.3 < X < 6.0 mg / cm 2 and is characterized by satisfying the above.
[0016] As a result of the intensive research conducted by the present inventors, it has become clear that a lithium metal composite oxide containing a specific metal element (Me) and having a molar ratio Li / Me between the metal element (Me) and lithium metal that satisfies a specific range, the lithium metal composite oxide has an inverse fluorite structure, and the content of the pre-doping agent containing the lithium metal composite oxide satisfies a specific range, thereby obtaining a pre-doped sheet for a storage device that is excellent in rate while maintaining electrode strength. When using a pre-doping agent, a technique is known in which the pre-doping agent is mixed in advance with an electrode and a voltage for initial charging is applied to pre-dope lithium ions, but the present invention overturns such technical common sense and makes it possible to effectively perform pre-doping without mixing it with an electrode. As a result, it is possible to provide a storage device that is excellent in rate while maintaining electrode strength, even compared to the case where a pre-doping agent is mixed with an electrode.
[0017] As is clear from the comparison between the following Examples and Comparative Examples, in the pre-doped sheets of Comparative Examples 1 and 2 obtained using a pre-doping agent that does not satisfy 3.0 < Li / Me (molar ratio) ≤ 7.5, as a result of the 90° bending test, peeling and powdering of the surface coated with the pre-doping agent were confirmed. In Comparative Example 5 using titanium (Ti) as the metal element (Me), although peeling and powdering of the surface did not occur as a result of the 90° bending test, in the production of a full cell (coin cell), the realization rate of the designed capacity at 1C decreased and the pre-doping was insufficient, and also the capacity retention rate at 10C with respect to 1C decreased (Comparative Example 16). Further, in Comparative Examples 6 to 14 in which the pre-doping agent was mixed into the positive electrode, as a result of the 90° bending test, peeling and powdering of the surface occurred in most cases (Comparative Examples 7 to 14), and even in the case of Comparative Example 6 where peeling and powdering of the surface did not occur, in the production of a full cell (coin cell), the realization rate of the designed capacity at 1C decreased and the pre-doping did not proceed well, and also the capacity retention rate at 10C with respect to 1C decreased (Comparative Example 17). On the other hand, in the pre-doped sheets of Examples 1 to 12 obtained using a pre-doping agent that satisfies 3.0 < Li / Me (molar ratio) ≤ 7.5, as a result of the 90° bending test, peeling and powdering of the surface did not occur, and in the production of a full cell (coin cell), since the realization rate of the designed capacity at 1C was high, the pre-doping proceeded sufficiently, and it was confirmed that the capacity retention rate at 10C with respect to 1C was also high. Therefore, the significance of adopting the above configuration is great, and with the pre-doped sheet of the present invention, pre-doping can be effectively performed without mixing the pre-doping agent into the electrode, so that it is possible to provide a power storage device that maintains electrode strength and is excellent in rate performance.
[0018] The lithium metal composite oxide used in the present invention contains lithium (Li) and at least one metal element (Me) selected from the group consisting of Fe, Al, Mn, and Co, satisfies 3.0 < Li / Me (molar ratio) ≤ 7.5, and has an inverse fluorite structure. By the metal element (Me) being at least one selected from the group consisting of Fe, Al, Mn, and Co, the lithium metal composite oxide containing lithium (Li) and the metal element (Me) has an inverse fluorite structure. Since the lithium metal composite oxide used in the present invention has such an inverse fluorite structure, lithium ions are likely to desorb, and after desorption, the crystal structure collapses and reinsertion of lithium ions does not occur, so it is considered that the pre-doping effect is enhanced. On the other hand, when the metal element (Me) is other than Fe, Al, Mn, and Co, there is a possibility that pre-doping becomes insufficient. The metal element (Me) is preferably at least one selected from the group consisting of Fe, Al, and Mn, and more preferably at least one selected from the group consisting of Fe and Mn.
[0019] The lithium metal composite oxide used in the present invention preferably has diffraction peak intensities at 2θ (diffraction angle) = 23.7 ± 0.5°, 33.6 ± 0.7°, 36.5 ± 0.7°, and 56.7 ± 0.5° in X-ray diffraction measurement. If it does not have any one of the diffraction peak intensities, the lithium metal composite oxide does not have an inverse fluorite structure, pre-doping becomes insufficient, and there is also a possibility that the capacity retention rate of 10C with respect to 1C decreases.
[0020] In the present invention, it is particularly important that the Li / Me (molar ratio) in the lithium metal composite oxide satisfies 3.0 < Li / Me ≤ 7.5. As a result of the study by the present inventors, among lithium metal composite oxides having an inverse fluorite structure, it has been clarified that a pre-doped sheet that can be suitably used as an electricity storage device excellent in rate performance while maintaining electrode strength can be provided by having a Li / Me (molar ratio) within a specific range. When the Li / Me (molar ratio) is 3.0 or less, the strength of the pre-doped sheet may decrease and the film thickness may increase. It is preferably 3.2 or more, more preferably 3.5 or more, still more preferably 3.8 or more, particularly preferably 4.2 or more, and most preferably 4.5 or more. On the other hand, when the Li / Me (molar ratio) exceeds 7.5, the strength of the pre-doped sheet may decrease and the rate performance of the resulting electricity storage device may decrease. It is preferably 7.3 or less, more preferably 6.8 or less, still more preferably 6.5 or less, and particularly preferably 6.2 or less.
[0021] The pre-doped sheet of the present invention requires that the content (X) of the pre-doping agent satisfies 0.3 < X < 6.0 mg / cm 2 When the content (X) of the pre-doping agent is 0.3 mg / cm 2 or less, pre-doping may be insufficient and the design capacity realization rate may decrease. It is preferably 0.35 mg / cm 2 or more, and more preferably 0.4 mg / cm 2 or more. On the other hand, when the content (X) of the pre-doping agent is 6.0 mg / cm 2 or more, the electrode strength may decrease and the capacity retention rate may decrease. It is preferably 5.5 mg / cm 2 or less, more preferably 4.8 mg / cm 2 or less, still more preferably 3.5 mg / cm 2 or less, particularly preferably 2.8 mg / cm 2 or less, and most preferably 1.5 mg / cm 2 or less.
[0022] The method for producing the pre-doping agent used in the present invention is not particularly limited.Mixing lithium raw material with at least one metal raw material selected from the group consisting of Fe raw material, Al raw material, Mn raw material and Co raw material (hereinafter, sometimes abbreviated as "mixing process"), and calcining in an oxygen-free atmosphere (hereinafter, sometimes abbreviated as "calcining process"), the pre-doping agent containing lithium metal composite oxide can be obtained.
[0023] The lithium raw material is not particularly limited, and lithium hydroxide, lithium carbonate, lithium acetate, lithium nitrate, lithium oxide, etc. are preferably used. These may be hydrated or anhydrous. Among them, lithium hydroxide is more preferably used.
[0024] The at least one metal raw material selected from the group consisting of the Fe raw material, Al raw material, Mn raw material, and Co raw material is not particularly limited, but specifically, the following examples are preferably used. These may be hydrated or anhydrous. Examples of the Fe raw material include iron oxide (II), iron oxide (III), iron oxide (II, III), iron oxide hydroxide (III), ferrous sulfate (II), ferric sulfate (III), iron hydroxide (II), and iron hydroxide (III). Examples of the Al raw material include aluminum oxide, aluminum hydroxide, aluminum sulfate, and aluminum nitrate. Examples of the Mn raw material include manganese oxide, manganese hydroxide, manganese carbonate, manganese sulfate, and manganese nitrate. Examples of the Co raw material include cobalt oxide, cobalt hydroxide, cobalt sulfate, and cobalt nitrate.
[0025] In the mixing step, a certain amount of carbon raw material is preferably blended. The carbon raw material is not particularly limited, and polyvinyl alcohol, activated carbon, acetylene black, ketjen black, carbon nanotubes, carbon nanofibers, graphene, etc. are preferably used. The blending amount of the carbon raw material is preferably 1 to 70 parts by weight with respect to 100 parts by weight of the total of the lithium raw material and the metal raw material. If the blending amount of the carbon raw material is less than 1 part by weight, the reaction between lithium and at least one metal element selected from the group consisting of Fe, Al, Mn, and Co becomes non-uniform, the resulting lithium metal composite oxide does not have an inverse fluorite structure, pre-doping becomes insufficient, and the capacity maintenance rate of 10C to 1C may also decrease. The blending amount of the carbon raw material is more preferably 5 parts by weight or more, and even more preferably 10 parts by weight or more. On the other hand, if the blending amount of the carbon raw material exceeds 70 parts by weight, the manufacturing cost becomes high, which is not preferable. The blending amount of the carbon raw material is more preferably 60 parts by weight or less, and even more preferably 50 parts by weight or less.
[0026] In the mixing step, the lithium raw material and the metal raw material are mixed, preferably including the carbon raw material. They may be mixed by a dry method or a wet method, but it is preferable to pulverize them when mixing. When pulverizing, a pulverizing device such as a ball mill, a planetary mill, a mortar mill, a jet mill, or a pin mill is preferably used.
[0027] In the firing step, it is preferable to perform firing in an oxygen-free atmosphere, for example, in an inert gas atmosphere, a hydrogen gas atmosphere, or a hydrogen-inert gas atmosphere, and nitrogen, argon, helium, neon, krypton, etc. are preferably used as the inert gas. In addition, the firing temperature in the firing step is preferably 650 to 1000 ° C. If the firing temperature is less than 650 ° C, unreacted raw materials remain, the resulting lithium metal composite oxide does not have an inverse fluorite structure, pre-doping becomes insufficient, and the capacity maintenance rate of 10 C to 1 C may also decrease. The firing temperature is more preferably 750 ° C or higher, and even more preferably 850 ° C or higher. If the firing temperature exceeds 1000 ° C, it becomes difficult to pulverize the resulting lithium metal composite oxide, the particles after pulverization become coarse, and the production of the pre-doped sheet may become difficult. The firing temperature is more preferably 980 ° C or lower.
[0028] The calcination time in the calcination step is preferably 2 to 80 hours. If the calcination time is less than 2 hours, unreacted raw materials remain, the resulting lithium metal composite oxide does not have an inverse fluorite structure, pre-doping becomes insufficient, and the capacity maintenance rate of 10C to 1C may also decrease. The calcination time is more preferably 10 hours or more, even more preferably 24 hours or more, and particularly preferably 48 hours or more. On the other hand, if the calcination time exceeds 80 hours, the productivity may decrease. The calcination time is more preferably 75 hours or less.
[0029] The lithium metal composite oxide obtained as described above can be used as a pre-doping agent to obtain a pre-doped sheet by forming it into a sheet. The method for producing the pre-doped sheet of the present invention is not particularly limited, but (1) a pre-doped sheet is produced by applying a coating material containing the pre-doping agent and an organic solvent to the surface of a porous sheet substrate (hereinafter, sometimes abbreviated as "production method 1") is a preferred embodiment, and (2) a pre-doped sheet is produced by kneading the pre-doping agent into a resin and molding it (hereinafter, sometimes abbreviated as "production method 2") is also a preferred embodiment. Furthermore, (3) a pre-doped sheet is produced by applying a coating material containing the pre-doping agent and an organic solvent to the surface of a release film substrate (hereinafter, sometimes abbreviated as "production method 3") is also a preferred embodiment.
[0030] The porous sheet substrate used in the manufacturing method 1 is not particularly limited as long as it can be formed into a sheet by applying a coating material containing the pre-dope agent and an organic solvent, but a film, a woven fabric, or a nonwoven fabric is preferably used. Examples of the material include polypropylene, polybutene, polyhexene, polyethylene fluoride, polyvinyl chloride, polyvinyl acetate, acetalized polyvinyl alcohol, ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-methylbutene copolymer, ethylene-methylpentene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, etc.
[0031] The organic solvent used is not particularly limited, and N-methyl-2-pyrrolidone or the like is preferably used, and the viscosity of the paint can be adjusted. In addition, in addition to the pre-dope agent and the organic solvent, the paint may contain, as a conductive assistant, one or a mixture of conductive materials such as natural graphite (scale graphite, flake graphite, earthy graphite, etc.), artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, metal (copper, nickel, aluminum, silver, etc.) powder or fiber, polyphenylene derivative, etc. In addition, the paint may contain, as a binder, one or a mixture of polyvinyl chloride, polyvinylpyrrolidone, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene butadiene rubber, polybutadiene, fluororubber, polyethylene oxide, etc. In coating the paint, the coating amount can be suitably adjusted using a bar coater, a knife coater, a roll coater, etc. In this way, the pre-doped sheet of the present invention can be suitably obtained. The coating pattern on the porous sheet substrate is not particularly limited, and may be coated on the entire surface of the sheet, but partial overlapping of any of stripes, frame shapes, disk shapes, lattice shapes, and dot shapes is also suitably used. The overlapping interval is preferably constant, but does not have to be constant.
[0032] The resin used in the manufacturing method 2 is not particularly limited, and resins such as polyolefins such as polyethylene and polypropylene; polyesters such as polyethylene terephthalate and polybutylene terephthalate; and polyamides such as nylon are preferably used. These resins may be monomers or copolymers. The pre-dope sheet of the present invention can be preferably obtained by kneading the resin and the pre-dope agent and forming it into a sheet by a doctor blade method, pressing, or stretching.
[0033] The release film substrate used in the manufacturing method 3 is not particularly limited as long as it is a substrate that can be formed into a sheet by applying a coating material containing the pre-dope agent and an organic solvent, but silicone-type release films and non-silicone-type release films are preferably used. Examples of the material include polypropylene, polybutene, polyhexene, polyethylene fluoride, polyvinyl chloride, polyvinyl acetate, acetalized polyvinyl alcohol, ethylene-propylene copolymer, ethylene-butene copolymer, ethylene-methylbutene copolymer, ethylene-methylpentene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer, polyethylene terephthalate, etc.
[0034] The organic solvent used is not particularly limited, and N-methyl-2-pyrrolidone or the like is preferably used to adjust the viscosity of the paint. In addition, in addition to the pre-dope agent and the organic solvent, the paint may contain, as a conductive assistant, one or a mixture of conductive materials such as natural graphite (scale graphite, flake graphite, clay graphite, etc.), artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, metal (copper, nickel, aluminum, silver, etc.) powder or fiber, polyphenylene derivative, etc. In addition, the paint may contain, as a binder, one or a mixture of polyvinyl chloride, polyvinylpyrrolidone, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, ethylene-propylene-diene terpolymer (EPDM), sulfonated EPDM, styrene butadiene rubber, polybutadiene, fluororubber, polyethylene oxide, silicone rubber, etc. In the coating of the coating material, the coating amount can be suitably adjusted using a bar coater, a knife coater, a roll coater, or the like. In this way, the pre-doped sheet of the present invention can be suitably obtained. The coating pattern on the release film substrate is not particularly limited, and may be applied to the entire surface of the sheet, but partial overlapping of any of stripes, frame shapes, disk shapes, lattice shapes, and dot shapes is also suitably used. The overlapping interval is preferably constant, but does not have to be constant.
[0035] The pre-doped sheet thus obtained is preferably arranged so as to contact the positive electrode from the viewpoint of effectively performing pre-doping. At this time, the pre-doped sheet may be arranged so as to contact the surface of the positive electrode, or the pre-doped sheet may be arranged so as to contact the back surface of the positive electrode. It is also preferable that the pre-doped sheet is arranged between the positive electrode and the negative electrode, and in particular, it has become clear by the present inventors that after the pre-doping process is performed by applying the voltage of the initial charge, the pre-doped sheet can become an insulator and therefore function as a separator. From this viewpoint, a separator for an electric storage device containing a pre-doped sheet is a preferred embodiment.
[0036] As described above, the pre-doped sheet of the present invention can effectively perform pre-doping without blending a pre-doping agent in the electrode, and has excellent rate properties while maintaining electrode strength compared to the case where a pre-doping agent is blended in the electrode. Therefore, a preferred embodiment is an electric storage device including a pre-doped sheet. The electric storage device is not particularly limited, and at least one type of electric storage device selected from the group consisting of a lithium ion battery, a lithium ion capacitor, and an electric double layer capacitor is preferred. EXAMPLES
[0037] The present invention will be described in more detail below using examples, but the present invention is not limited to these examples.
[0038] [Preparation of pre-dopant] Examples of preparation of lithium metal composite oxides used as pre-dopants are shown in Samples 1 to 7 and Comparative Samples 1 and 2. Each sample was handled in an environment where it was less affected by atmospheric humidity. [X-ray diffraction measurement] Materials with an inverse fluorite structure commonly have clear peaks at 2θ (diffraction angle) = 23.7 ± 0.5°, 33.6 ± 0.7°, 36.5 ± 0.7°, and 56.7 ± 0.5°. X-ray diffraction measurements were performed on the obtained samples 1 to 7 and comparison samples 1 and 2. X-ray diffraction measurements were performed using a Philips XRD device "X'pert-PRO" using Cu Kα radiation to measure each of the prepared samples, and the peak positions are shown in Table 1 only if peaks exist at the corresponding positions.
[0039] (Sample 1: Li / Fe=4.9) Iron oxide (Aldrich, Fe3O4) and lithium hydroxide monohydrate (Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a molar ratio of Li:Fe=5.0:1, and the same weight of polyvinyl alcohol (Aldrich) was added to a planetary ball mill and ground and mixed for 9 hours. The mixture was removed and fired at 950°C for 72 hours in a nitrogen atmosphere of 2L / min in a box-shaped electric furnace. The fired product was ground in a hammer mill, and then coarse particles were removed using a sieve with 100μm openings to obtain Sample 1, a pre-dopant containing lithium metal composite oxide (Li / Fe=4.9) with the metal species Fe.
[0040] [ICP measurement] 10 mL of sulfuric acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., 98% for precision analysis) was added to 0.05 g of the above sample 1 (pre-dopant), and water was added dropwise while heating with a heater at 200 °C to completely dissolve it. The concentrations of lithium and metal species in the obtained pre-dopant sulfuric acid solution were calculated to be about 1 to 2 ppm, and the measurement solution was prepared by diluting with water. The prepared solution was measured using an ICP emission spectrometer (SPECTRO ARCOS EOP). From the ICP measurement results, the content of Li in sample 1 was 22 wt%, and Li / Fe was 4.9. The measurement results are shown in Table 1.
[0041] (Sample 2: Li / Fe=7.2) Sample 2 was obtained as a pre-dopant containing a lithium metal composite oxide (Li / Fe=7.2) with the metal species of Fe, in the same manner as Sample 1, except that the molar ratio of iron oxide and lithium hydroxide monohydrate was Li:Fe=7.4:1. The sulfuric acid solution concentration of the obtained Sample 2 was diluted to the same concentration as Sample 1 and ICP measurement was performed, and the Li content in the pre-dopant of Sample 2 was 28wt%, and the Li / Fe ratio was 7.2. The measurement results are shown in Table 1.
[0042] (Sample 3: Li / Fe=7.8) Sample 3 was obtained as a pre-dopant containing a lithium metal composite oxide (Li / Fe=7.8) with the metal species of Fe, in the same manner as Sample 1, except that the molar ratio of iron oxide and lithium hydroxide monohydrate was Li:Fe=8.0:1. The sulfuric acid solution concentration of the obtained Sample 3 was diluted to the same concentration as Sample 1 and ICP measurement was performed, and the Li content in the pre-dopant of Sample 3 was 29wt%, and the Li / Fe ratio was 7.8. The measurement results are shown in Table 1.
[0043] (Sample 4: Li / Fe=2.2) Sample 4 was obtained as a pre-dopant containing a lithium metal composite oxide (Li / Fe=2.2) with the metal species of Fe, in the same manner as Sample 1, except that the molar ratio of iron oxide and lithium hydroxide monohydrate was Li:Fe=2.4:1. The sulfuric acid solution concentration of the obtained Sample 4 was diluted to the same concentration as Sample 1 and ICP measurement was performed, and the Li content in the pre-dopant of Sample 4 was 9wt%, and the Li / Fe ratio was 2.2. The measurement results are shown in Table 1.
[0044] (Sample 5: Li / Mn=5.9) Sample 5 was obtained as a pre-dopant containing lithium metal composite oxide (Li / Mn=5.9) with the metal species Mn, in the same manner as Sample 1, except that manganese oxide (MnO2, manufactured by Aldrich) was used instead of iron oxide, and the molar ratio of manganese oxide and lithium hydroxide monohydrate was Li:Mn=6:1. The sulfuric acid solution concentration of the obtained Sample 5 was diluted to the same concentration as Sample 1 and ICP measurement was performed, and the Li content in the pre-dopant of Sample 5 was 24wt%, and Li / Mn was 5.9. The measurement results are shown in Table 1.
[0045] (Sample 6: Li / Co=5.8) Sample 6 was obtained as a pre-dopant containing lithium metal composite oxide (Li / Co=5.8) whose metal species is Co, in the same manner as Sample 1, except that cobalt oxide (Aldrich, CoO) was used instead of iron oxide, and the molar ratio of cobalt oxide and lithium hydroxide monohydrate was Li:Co=6.0:1. The sulfuric acid solution concentration of the obtained Sample 6 was diluted to the same concentration as Sample 1 and ICP measurement was performed, and the Li content in the pre-dopant of Sample 6 was 24wt%, and Li / Co was 5.8. The measurement results are shown in Table 1.
[0046] (Sample 7: Li / Al=4.9) Sample 7 was obtained as a pre-dopant containing lithium metal composite oxide (Li / Al=4.9) with the metal species of Al, in the same manner as Sample 1, except that aluminum oxide (Al2O3, manufactured by Aldrich) was used instead of iron oxide, and the molar ratio of aluminum oxide and lithium hydroxide monohydrate was Li:Al=5.0:1. The sulfuric acid solution concentration of the obtained Sample 7 was diluted to the same concentration as Sample 1 and ICP measurement was performed, and the Li content in the pre-dopant of Sample 7 was 18wt%, and Li / Al was 4.9. The measurement results are shown in Table 1.
[0047] (Comparative sample 1) Iron oxide (Aldrich, Fe3O4) and lithium hydroxide monohydrate (Fujifilm Wako Pure Chemical Industries, Ltd.) were weighed out to a molar ratio of Li:Fe=5.0:1, and then put into a planetary ball mill and ground and mixed for 9 hours to obtain Comparative Sample 1. The sulfuric acid solution concentration of the obtained Comparative Sample 1 was diluted to the same concentration as Sample 1 and ICP measurement was performed. The Li content in the pre-dopant of Comparative Sample 1 was 12wt%, and the Li / Fe ratio was 5.0. The measurement results are shown in Table 1.
[0048] (Comparative sample 2) Comparative sample 2 was obtained in the same manner as sample 1, except that anatase-type titanium oxide (TiO2, manufactured by Aldrich) was used instead of iron oxide, and the molar ratio of anatase-type titanium oxide and lithium hydroxide monohydrate was Li:Ti=4.0:1. The sulfuric acid solution concentration of the obtained comparative sample 2 was diluted to the same concentration as sample 1 and ICP measurement was performed, and the Li content in the pre-dopant of comparative sample 2 was 20wt%, and Li / Ti was 4.0. The measurement results are shown in Table 1.
[0049] [Preparation and evaluation of pre-doped sheets] Example 1 Sample 1 was used as a pre-dopant, acetylene black (Denka Black, manufactured by Denka Co., Ltd.) as a conductive assistant, polyvinylidene fluoride (KF Polymer #9130, manufactured by Kureha Co., Ltd.) as a binder was added to these, kneaded using a centrifugal mixer, and the viscosity was adjusted with N-methyl-2-pyrrolidone (NMP) to obtain a paint. The mass ratio of pre-dopant / conductive assistant / binder was 85 / 5 / 10. Next, the prepared paint was applied to a cellulose-based nonwoven fabric (TF40, manufactured by Nippon Kodoshi Co., Ltd.), which is a porous sheet substrate, using a bar coater, and a pre-doped sheet was obtained by punching out the material to a size of φ16.
[0050] [Evaluation of pre-dopant amount and capacitance (Li amount)] From the weight of the obtained pre-doped sheet, the amount of pre-doping agent (coating amount) was 0.5 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated as follows, and it was confirmed that 0.9 mAh of Li was present. The calculation method is shown below. Electrode weight - Base material weight = Solid content weight Solid weight × Pre-dope % = Pre-dope weight Pre-dopant weight x lithium content (measured by ICP) = lithium weight Lithium weight ÷ lithium molecular weight = lithium moles Now, from the Faraday constant, 96485C / mol=26.801mAh / mmol Lithium moles x 26.801mAh / mmol = capacity mAh (amount of Li)
[0051] [90° bending test] The pre-doped sheet cut to a width of about 5 cm x 10 cm was held by hand at both ends so that the coated surface was facing upward, and pressed against a cylindrical iron rod with a diameter of 1 cm. The pre-doped sheet or electrode was bent 90° with the part touching the rod as the apex, and peeling of the coated surface was visually confirmed (see FIG. 1). During the test, a blank sheet of paper was placed underneath to check for powder falling. Those in which peeling or powder falling was confirmed were listed as B, and those in which it was not confirmed were listed as A in Table 2. A 90° bending test was performed on the pre-doped sheet obtained in Example 1 above, and no peeling or powder falling occurred. The results are shown in Table 2.
[0052] Example 2 A pre-doped sheet was obtained in the same manner as in Example 1, except that Sample 2 was used as the pre-doping agent instead of Sample 1 in Example 1. From the weight of the obtained pre-doped sheet, the amount of the pre-doping agent (coating amount) was 0.5 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that Li was present for 1.1 mAh. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0053] Example 3 A pre-doped sheet was obtained in the same manner as in Example 1, except that the coating amount of the paint on the porous sheet substrate was changed by changing the bar coater used in Example 1. From the weight of the obtained pre-doped sheet, the amount of pre-doping agent (coating amount) was 0.7 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that 1.2 mAh of Li was present. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0054] Example 4 A pre-doped sheet was obtained in the same manner as in Example 1, except that the coating amount of the paint on the porous sheet substrate was changed by changing the bar coater used in Example 1. From the weight of the obtained pre-doped sheet, the amount of pre-doping agent (coating amount) was 2.7 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that Li was present for 4.6 mAh. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0055] Example 5 A pre-doped sheet was obtained in the same manner as in Example 1, except that the coating amount of the paint on the porous sheet substrate was changed by changing the bar coater used in Example 1. From the weight of the obtained pre-doped sheet, the amount of pre-doping agent (coating amount) was 4.7 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that 8.1 mAh of Li was present. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0056] Example 6 A pre-doped sheet was obtained in the same manner as in Example 1, except that the coating amount of the paint on the porous sheet substrate was changed by changing the bar coater used in Example 1. From the weight of the obtained pre-doped sheet, the amount of pre-doping agent (coating amount) was 0.4 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that 0.7mAh of Li was present. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0057] Example 7 A pre-doped sheet was obtained in the same manner as in Example 1, except that the porous sheet substrate used was changed to a polyester nonwoven fabric (Nippon Vilene). From the weight of the obtained pre-doped sheet, the amount of pre-doping agent (coating amount) was 0.5 mg / cm 2The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that 0.8mAh of Li was present. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0058] Example 8 A pre-doped sheet was obtained in the same manner as in Example 1, except that the porous sheet substrate used was changed to a polyolefin film (manufactured by Asahi Kasei, Hypore Separator). From the weight of the obtained pre-doped sheet, the amount of pre-doping agent (coating amount) was 0.5 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that 0.8mAh of Li was present. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0059] Example 9 A pre-doped sheet was obtained in the same manner as in Example 1, except that Sample 5 was used as the pre-doping agent instead of Sample 1 in Example 1. From the weight of the obtained pre-doped sheet, the amount of the pre-doping agent (coating amount) was 0.5 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that Li was present for 1.0 mAh. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0060] Example 10 A pre-doped sheet was obtained in the same manner as in Example 1, except that Sample 6 was used as the pre-doping agent instead of Sample 1 in Example 1. From the weight of the obtained pre-doped sheet, the amount of the pre-doping agent (coating amount) was 0.5 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that 0.9mAh of Li was present. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0061] Example 11 A pre-doped sheet was obtained in the same manner as in Example 1, except that Sample 7 was used as the pre-doping agent instead of Sample 1 in Example 1. From the weight of the obtained pre-doped sheet, the amount of the pre-doping agent (coating amount) was 0.6 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that 1.3 mAh of Li was present. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0062] Example 12 1 g of sample 1 was added to 5 g of a 5 wt% toluene solution of granular polyethylene (NUC, EVA COPOLYMER), and then the mixture was kneaded at 40°C using a planetary centrifugal mixer. The mixture obtained was applied to a glass plate using a doctor blade method, dried with hot air from a dryer, and peeled off from the edge to obtain a film-like pre-doped sheet. The amount of pre-doping agent (coating amount) and the amount of Li were calculated by measuring the obtained film directly with ICP, and the amount of pre-doping agent was 0.6 mg / cm. 2 The presence of Li for 1.0 mAh was confirmed. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0063] (Example 13) Sample 1 was used as a pre-dopant, acetylene black (Denka Black, manufactured by Denka Co., Ltd.) as a conductive assistant, polyvinylidene fluoride (KF Polymer #9130, manufactured by Kureha Co., Ltd.) as a binder was added to these, kneaded using a centrifugal mixer, and the viscosity was adjusted with N-methyl-2-pyrrolidone (NMP) to obtain a paint. The mass ratio of pre-dopant / conductive assistant / binder was 95 / 2 / 3. Next, the prepared paint was applied to a silicone type release film (HY-S30-2, manufactured by Higashiyama Film Co., Ltd.), which is a release film substrate, using a bar coater, and a pre-doped sheet was obtained by punching out to a size of φ16. The amount of pre-dopant (coating amount) and the amount of Li were calculated by measuring the obtained film as it is with ICP, and the amount of pre-dopant was 0.5 mg / cm. 2 The presence of Li for 0.9 mAh was confirmed. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0064] Example 14 A pre-doped sheet was obtained in the same manner as in Example 13, except that the coating amount of the paint was changed. The amount of the pre-doping agent (coating amount) and the amount of Li were calculated by measuring the obtained film directly with ICP, and the amount of the pre-doping agent was 2.7 mg / cm. 2 The presence of Li for 4.6 mAh was confirmed. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0065] Example 15 A pre-doped sheet was obtained in the same manner as in Example 13, except that the coating amount of the paint was changed. The amount of the pre-doping agent (coating amount) and the amount of Li were calculated by measuring the obtained film directly with ICP, and the amount of the pre-doping agent was 4.7 mg / cm. 2 The presence of Li for 8.1 mAh was confirmed. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0066] Comparative Example 1 A pre-doped sheet was obtained in the same manner as in Example 1, except that Sample 4 was used as a pre-doping agent instead of Sample 1, and the coating amount of the paint on the porous sheet substrate was changed by changing the bar coater used. From the weight of the obtained pre-doped sheet, the amount of the pre-doping agent (coating amount) was 6.6 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that 4.6mAh of Li was present. A 90° bending test was performed on the obtained pre-doped sheet, and peeling of the coating surface was confirmed. The results are shown in Table 2.
[0067] Comparative Example 2 A pre-doped sheet was obtained in the same manner as in Example 1, except that Sample 3 was used as a pre-doping agent instead of Sample 1, and the coating amount of the paint on the porous sheet substrate was changed by changing the bar coater used. From the weight of the obtained pre-doped sheet, the amount of the pre-doping agent (coating amount) was 2.0 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that 4.6mAh of Li was present. A 90° bending test was performed on the obtained pre-doped sheet, and peeling and powder falling off of the coating surface were confirmed. The results are shown in Table 2.
[0068] Comparative Example 3 A pre-doped sheet was obtained in the same manner as in Example 1, except that the coating amount of the paint on the porous sheet substrate was changed by changing the bar coater used in Example 1. From the weight of the obtained pre-doped sheet, the amount of pre-doping agent (coating amount) was 6.0 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that Li was present for 10.2 mAh. When the obtained pre-doped sheet was subjected to a 90° bending test, powder fell off. The results are shown in Table 2.
[0069] Comparative Example 4 A pre-doped sheet was obtained in the same manner as in Example 1, except that Comparative Sample 1 was used as a pre-doping agent instead of Sample 1, and the coating amount of the paint on the porous sheet substrate was changed by changing the bar coater used. From the weight of the obtained pre-doped sheet, the amount of pre-doping agent (coating amount) was 2.6 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that 1.2 mAh of Li was present. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0070] Comparative Example 5 A pre-doped sheet was obtained in the same manner as in Example 1, except that Comparative Sample 2 was used as a pre-doping agent instead of Sample 1, and the coating amount of the paint on the porous sheet substrate was changed by changing the bar coater used. From the weight of the obtained pre-doped sheet, the amount of pre-doping agent (coating amount) was 1.4 mg / cm 2 The amount of Li present on the pre-doped sheet was calculated, and it was confirmed that Li was present for 1.1 mAh. When the obtained pre-doped sheet was subjected to a 90° bending test, no peeling or powder falling occurred. The results are shown in Table 2.
[0071] [Preparation and evaluation of pre-dopant mixed cathode] Comparative Example 6 Sample 1 was used as a pre-dope agent, activated carbon (YP50F, manufactured by Kuraray Co., Ltd.) as a positive electrode active material, and acetylene black (Denka Co., Ltd., Denka Black) as a conductive assistant. These were added to polyvinylidene fluoride (KF Polymer #9130, manufactured by Kureha Co., Ltd.) as a binder, kneaded using a rotation-revolution mixer, and the viscosity was adjusted with N-methyl-2-pyrrolidone (NMP) to obtain a positive electrode paint. The mass ratio of pre-dope agent / positive electrode active material / conductive assistant / binder was 7 / 70 / 9 / 14. Next, the prepared positive electrode paint was applied to one side of an etched aluminum foil (JCC-20CB, manufactured by Nippon Chemi-Conductor Industrial Co., Ltd.) as a current collector, dried at 130 ° C for 30 minutes, and then roll pressed with a 0.01 mm slit to prepare a pre-dope agent mixed positive electrode. At this time, the theoretical capacity of the activated carbon was calculated as 40 mAh / g, and the coating thickness was adjusted so that 0.2 mAh of activated carbon was coated when punched with a φ15 punch. From the weight of the obtained pre-dope agent mixed positive electrode, the amount of pre-dope agent (coating amount) was 0.2 mg / cm 2 It was estimated that 0.4mAh of Li was present. When a 90° bending test was performed on the pre-dopant mixed positive electrode, peeling and powder falling did not occur. The results are shown in Table 3.
[0072] Comparative Example 7 In Comparative Example 6, a pre-dope agent mixed positive electrode was obtained in the same manner as in Comparative Example 6, except that the mass ratio of the pre-dope agent / positive electrode active material / conductive assistant / binder was 8 / 69 / 9 / 14. From the weight of the obtained pre-dope agent mixed positive electrode, the amount of the pre-dope agent (coating amount) was 0.3 mg / cm 2 It was estimated that 0.5mAh of Li was present. A 90° bending test was performed on the pre-dopant mixed positive electrode, and peeling of the coating surface was confirmed. The results are shown in Table 3.
[0073] Comparative Example 8 In Comparative Example 6, a pre-dope agent mixed positive electrode was obtained in the same manner as in Comparative Example 6, except that the mass ratio of the pre-dope agent / positive electrode active material / conductive assistant / binder was 11 / 66 / 9 / 14. From the weight of the obtained pre-dope agent mixed positive electrode, the amount of the pre-dope agent (coating amount) was 0.4 mg / cm2 It was estimated that 0.7mAh of Li was present. When a 90° bending test was performed on the pre-dopant mixed positive electrode, peeling of the coating surface and powder falling were confirmed. The results are shown in Table 3.
[0074] Comparative Example 9 In Comparative Example 6, a pre-dope agent mixed positive electrode was obtained in the same manner as in Comparative Example 6, except that the mass ratio of the pre-dope agent / positive electrode active material / conductive assistant / binder was 17 / 60 / 9 / 14. From the weight of the obtained pre-dope agent mixed positive electrode, the amount of the pre-dope agent (coating amount) was 0.7 mg / cm 2 It was estimated that 1.2mAh of Li was present. The surface of the obtained pre-dopant mixed positive electrode peeled off when pressed, so a 90° bending test was not performed. The results are shown in Table 3.
[0075] Comparative Example 10 A pre-dope agent mixed positive electrode was obtained in the same manner as in Comparative Example 6, except that Sample 3 was used as a pre-dope agent instead of Sample 1. From the weight of the obtained pre-dope agent mixed positive electrode, the amount of the pre-dope agent (coating amount) was 0.2 mg / cm 2 It was estimated that 0.5mAh of Li was present. A 90° bending test was performed on the pre-dopant mixed positive electrode, and peeling of the coating surface was confirmed. The results are shown in Table 3.
[0076] Comparative Example 11 Sample 1 was used as a pre-dopant, activated carbon (YP50F, Kuraray Co., Ltd.) as a positive electrode active material, and acetylene black (Denka Co., Ltd., Denka Black) as a conductive assistant. These were added to a 1% by mass aqueous solution of carboxymethylcellulose (H-1496B, Daiichi Kogyo Seiyaku Co., Ltd.) as a thickener, and kneaded using a rotation / revolution mixer to obtain a kneaded material. Next, styrene butadiene rubber (JSR Co., Ltd.) as a binder was added to the kneaded material to prepare a paint for the positive electrode, and the viscosity was adjusted with water. The mass ratio of the pre-dopant / positive electrode active material / conductive assistant / thickener / binder was 9 / 73 / 9 / 4 / 5. When the obtained paint for the positive electrode was applied to an Al current collector, the Al was corroded and hydrogen gas was generated. The pre-dopant mixed positive electrode obtained by drying had unevenness on the electrode surface due to the generated air bubbles. From the weight of the obtained pre-dope agent mixed positive electrode, the amount of pre-dope agent (coating amount) was 0.6 mg / cm 2 It was estimated that there was 0.4mAh of Li. In addition, a 90° bending test was not performed because the coating surface peeled off when pressed.
[0077] Comparative Example 12 A pre-dope agent mixed positive electrode was obtained in the same manner as in Comparative Example 7, except that Sample 5 was used as the pre-dope agent instead of Sample 1. From the weight of the obtained pre-dope agent mixed positive electrode, the amount of the pre-dope agent (coating amount) was 0.3 mg / cm 2 It was estimated that 0.4mAh of Li was present. A 90° bending test was performed on the pre-dopant mixed positive electrode, and peeling of the coating surface was confirmed. The results are shown in Table 3.
[0078] Comparative Example 13 A pre-dope agent mixed positive electrode was obtained in the same manner as in Comparative Example 7, except that Sample 6 was used as the pre-dope agent instead of Sample 1. From the weight of the obtained pre-dope agent mixed positive electrode, the amount of the pre-dope agent (coating amount) was 0.3 mg / cm 2 It was estimated that 0.4mAh of Li was present. A 90° bending test was performed on the pre-dopant mixed positive electrode, and peeling of the coating surface was confirmed. The results are shown in Table 3.
[0079] Comparative Example 14 A pre-dope agent mixed positive electrode was obtained in the same manner as in Comparative Example 7, except that Sample 7 was used as the pre-dope agent instead of Sample 1. From the weight of the obtained pre-dope agent mixed positive electrode, the amount of the pre-dope agent (coating amount) was 0.3 mg / cm 2 It was estimated that 0.3mAh of Li was present. A 90° bending test was performed on the pre-dopant mixed positive electrode, and peeling of the coating surface was confirmed. The results are shown in Table 3.
[0080] [Fabrication and evaluation of full cells (coin cells)] Example 16 A full cell was fabricated using the pre-doped sheet prepared in Example 3 as a separator, and a charge / discharge test was carried out. The fabrication method and evaluation method are described below.
[0081] (1) Preparation of the negative electrode First, graphite (Nippon Graphite Industries Co., Ltd., CGB-20) was used as the negative electrode active material, and acetylene black (Denka Co., Ltd., Denka Black) was used as the conductive assistant. These were added to a 1% by mass aqueous solution of carboxymethylcellulose (Dai-ichi Kogyo Seiyaku Co., Ltd., H-1496B) as a thickener, and the mixture was kneaded using a rotation and revolution mixer to obtain a kneaded product, and the viscosity was adjusted with water. Next, styrene butadiene rubber (JSR) as a binder was added to the kneaded product, and the mixture was further kneaded using a rotation and revolution mixer to prepare a paint for the negative electrode. The mass ratio of the negative electrode active material / conductive assistant / thickener / binder was 95 / 1 / 1 / 3. Finally, the paint for the negative electrode was applied to one side of a copper foil (Fukuda Metal Foil and Powder Co., Ltd.) as a current collector, dried at 100°C for 30 minutes, and then roll pressed with a 0.01 mm slit to prepare a negative electrode.
[0082] (2) Preparation of the positive electrode Activated carbon (YP-50F, Kuraray Co., Ltd.) was used as the positive electrode active material, and acetylene black (Denka Co., Ltd., Denka Black) was used as the conductive assistant. These were added to polyvinylidene fluoride (KF Polymer #9130, Kureha Co., Ltd.) as the binder, and the mixture was kneaded using a centrifugal mixer. The viscosity was adjusted with N-methyl-2-pyrrolidone to prepare a positive electrode paint. The mass ratio of positive electrode active material / conductive assistant / binder was 77 / 9 / 14. Next, the prepared positive electrode paint was applied to one side of an etched aluminum foil (JCC-20CB, Nippon Chemi-Con Corporation) as a current collector, dried at 130°C for 30 minutes, and then roll pressed with a 0.01 mm slit to prepare a positive electrode. At this time, the theoretical capacity of the activated carbon was calculated to be 40 mAh / g, and the coating thickness was adjusted so that 0.2 mAh of activated carbon was coated when punched out with a φ15 punch.
[0083] (3) Cell design Since the capacity of the positive electrode prepared above was 0.2 mAh, a negative electrode in which the capacity ratio of N (negative electrode active material) / P (positive electrode active material) was close to 10, i.e., a 2.0 mAh graphite-coated negative electrode, was used.
[0084] (4) Cell preparation The pre-doped sheet prepared in Example 3 was punched out to a size of φ16, and the coated surface of the pre-doping agent was placed so as to face the positive electrode surface, and the negative electrode was placed on the separator. A 2032-type coin cell was prepared by using an electrolyte (1.0M LiBF4 / PC) in which 1 mole of LiBF4 was added to 1 L of PC (propylene carbonate) solvent. The total thickness of the positive electrode and separator at this time was 129 μm.
[0085] (5) Charge / discharge test A pre-doping operation was performed using the coin cell. Specifically, the cell was charged to 4.5 V at a rate of 0.1 C based on activated carbon, and then the potential was held for 24 hours by constant voltage operation. After that, the cell was discharged to 2.2 V at 1 C, and then operated for three cycles at 1 C between 3.8 and 2.2 V, and then charged and discharged for three cycles at 10 C. As a result of the charge and discharge test, the discharge capacity at the third cycle was 0.19 mAh at 1 C and 0.15 mAh at 10 C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 95% at 1 C and 75% at 10 C. The results are shown in Table 4. A three-minute rest was given between each charge and discharge. The measurements were performed using Hokuto Denko Corporation's HJ1001SD8.
[0086] (Example 17) In Example 16, the coin cell was prepared and the charge / discharge test was performed in the same manner as in Example 16, except that the pre-doped sheet prepared in Example 5 was used as the separator. The total thickness of the positive electrode and the separator at this time was 140 μm. As a result, the discharge capacity at the third cycle was 0.22 mAh at 1C and 0.14 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 110% at 1C and 70% at 10C. The results are shown in Table 4.
[0087] (Example 18) In Example 16, the coin cell was prepared and the charge / discharge test was performed in the same manner as in Example 16, except that the pre-doped sheet prepared in Example 6 was used as the separator. The total film thickness of the positive electrode and the separator at this time was 123 μm. As a result, the discharge capacity at the third cycle was 0.15 mAh at 1C and 0.12 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 75% at 1C and 60% at 10C. The results are shown in Table 4.
[0088] (Example 19) In Example 16, the pre-doped sheet prepared in Example 12 was placed between the positive electrode and the separator, and a cellulose-based nonwoven fabric (TF40, manufactured by Nippon Kodoshi Kogyo Co., Ltd.) was used as the separator. The same procedure as in Example 16 was used to prepare a coin cell and perform a charge-discharge test. The total thickness of the positive electrode, separator, and pre-doped sheet at this time was 128 μm. As a result, the discharge capacity at the third cycle was 0.19 mAh at 1C and 0.12 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 95% at 1C and 60% at 10C. The results are shown in Table 4.
[0089] (Example 20) In Example 16, the pre-doped sheet prepared in Example 3 was placed on the back of the positive electrode, and a cellulose-based nonwoven fabric (manufactured by Nippon Kodoshi Kogyo Co., Ltd., TF40) was used as the separator. The same procedure as in Example 16 was used to prepare a coin cell and perform a charge-discharge test. The total thickness of the pre-doped sheet, positive electrode, and separator was 149 μm. As a result, the discharge capacity at the third cycle was 0.20 mAh at 1C and 0.16 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 100% at 1C and 80% at 10C. The results are shown in Table 4.
[0090] Example 21 In Example 16, except that the pre-doped sheet prepared in Example 9 was used, the coin cell was prepared and the charge / discharge test was performed in the same manner as in Example 16. The total film thickness of the positive electrode and the separator at this time was 127 μm. As a result, the discharge capacity at the third cycle was 0.19 mAh at 1 C and 0.15 mAh at 10 C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 95% at 1 C and 75% at 10 C. The results are shown in Table 4.
[0091] Example 22 In Example 16, the pre-doped sheet prepared in Example 13 was placed on the surface of the positive electrode, and only the pre-doped layer was transferred to the surface of the positive electrode using a roll press. The same procedure as in Example 16 was used to prepare a coin cell and perform a charge-discharge test. The total thickness of the positive electrode, separator, and pre-doped sheet at this time was 126 μm. As a result, the discharge capacity at the third cycle was 0.19 mAh at 1C and 0.17 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 95% at 1C and 85% at 10C. The results are shown in Table 4.
[0092] (Example 23) In Example 16, the pre-doped sheet prepared in Example 14 was placed on the surface of the positive electrode, and only the pre-doped layer was transferred to the surface of the positive electrode using a roll press. The same procedure as in Example 16 was used to prepare a coin cell and perform a charge-discharge test. The total thickness of the positive electrode, separator, and pre-doped sheet at this time was 133 μm. As a result, the discharge capacity at the third cycle was 0.20 mAh at 1C and 0.15 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 100% at 1C and 75% at 10C. The results are shown in Table 4.
[0093] Example 24 In Example 16, the pre-doped sheet prepared in Example 15 was placed on the surface of the positive electrode, and only the pre-doped layer was transferred to the surface of the positive electrode using a roll press. The same procedure as in Example 16 was used to prepare a coin cell and perform a charge-discharge test. The total thickness of the positive electrode, separator, and pre-doped sheet at this time was 133 μm. As a result, the discharge capacity at the third cycle was 0.20 mAh at 1C and 0.13 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 100% at 1C and 65% at 10C. The results are shown in Table 4.
[0094] Comparative Example 15 In Example 16, except that the pre-doped sheet prepared in Comparative Example 4 was used, the coin cell was prepared and the charge / discharge test was performed in the same manner as in Example 16. The total thickness of the positive electrode and the separator at this time was 135 μm. As a result, the discharge capacity at the third cycle was 0.05 mAh at 1C and 0.02 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 25% at 1C and 10% at 10C. The results are shown in Table 4.
[0095] Comparative Example 16 In Example 16, except that the pre-doped sheet prepared in Comparative Example 5 was used, the coin cell was prepared and the charge / discharge test was performed in the same manner as in Example 16. The total thickness of the positive electrode and the separator at this time was 128 μm. As a result, the discharge capacity at the third cycle was 0.04 mAh at 1C and 0.02 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 20% at 1C and 10% at 10C. The results are shown in Table 4.
[0096] Comparative Example 17 In Example 16, a coin cell was prepared and a charge / discharge test was performed in the same manner as in Example 16, except that the pre-dope agent mixed positive electrode prepared in Comparative Example 6 was used as the positive electrode and a cellulose-based nonwoven fabric (TF40, manufactured by Nippon Kodoshi Kogyo Co., Ltd.) was used as the separator. The total thickness of the positive electrode and the separator at this time was 122 μm. As a result, the discharge capacity at the third cycle was 0.08 mAh at 1C and 0.04 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 40% at 1C and 20% at 10C. The results are shown in Table 4.
[0097] (Comparative Example 18) In Example 16, a coin cell was prepared and a charge / discharge test was performed in the same manner as in Example 16, except that the pre-dope agent mixed positive electrode prepared in Comparative Example 7 was used as the positive electrode and a cellulose-based nonwoven fabric (TF40, manufactured by Nippon Kodoshi Kogyo Co., Ltd.) was used as the separator. The total thickness of the positive electrode and the separator at this time was 124 μm. As a result, the discharge capacity at the third cycle was 0.09 mAh at 1C and 0.04 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 45% at 1C and 20% at 10C. The results are shown in Table 4.
[0098] Comparative Example 19 In Example 16, a coin cell was prepared and a charge / discharge test was performed in the same manner as in Example 16, except that the pre-dope agent mixed positive electrode prepared in Comparative Example 8 was used as the positive electrode, and a cellulose-based nonwoven fabric (TF40, manufactured by Nippon Kodoshi Kogyo Co., Ltd.) was used as the separator. The total thickness of the positive electrode and the separator at this time was 128 μm. As a result, the discharge capacity at the third cycle was 0.10 mAh at 1C and 0.05 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 50% at 1C and 25% at 10C. The results are shown in Table 4.
[0099] Comparative Example 20 In Example 16, a coin cell was prepared and a charge / discharge test was performed in the same manner as in Example 16, except that the pre-dope agent mixed positive electrode prepared in Comparative Example 9 was used as the positive electrode and a cellulose-based nonwoven fabric (TF40, manufactured by Nippon Kodoshi Kogyo Co., Ltd.) was used as the separator. The total thickness of the positive electrode and the separator at this time was 137 μm. As a result, the discharge capacity at the third cycle was 0.18 mAh at 1C and 0.07 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 90% at 1C and 35% at 10C. The results are shown in Table 4.
[0100] Comparative Example 21 In Example 16, except that a cellulose-based nonwoven fabric (TF40, manufactured by Nippon Kodoshi Kogyo Co., Ltd.) was used as the separator, the same procedure as in Example 16 was used to prepare a coin cell and perform a charge-discharge test. The total thickness of the positive electrode and separator at this time was 114 μm. As a result, the discharge capacity at the third cycle was 0.05 mAh at 1C and 0.02 mAh at 10C. Since the design capacity was 0.2 mAh, the realization rate of the design capacity was 25% at 1C and 10% at 10C. The results are shown in Table 4.
[0101] [Table 1]
[0102] [Table 2]
[0103] [Table 3]
[0104] [Table 4] [Explanation of symbols]
[0105] 1 Pre-doped sheet or electrode 2 Iron rod (diameter 1.0 cm)
Claims
1. A pre-doped sheet for an electricity storage device, comprising a pre-doping agent containing a lithium metal composite oxide, The lithium metal composite oxide contains lithium (Li) and at least one metal element (Me) selected from the group consisting of Fe, Al, Mn, and Co, The lithium metal composite oxide has an inverse fluorite structure, The Li / Me (molar ratio) in the lithium metal composite oxide satisfies 3.0<Li / Me≦7.5, The content (X) of the pre-dopant is 0.3<X<6.0 mg / cm 2 A pre-doped sheet for an electricity storage device, comprising:
2. 2. The pre-doped sheet according to claim 1, wherein in an X-ray diffraction measurement, the lithium metal composite oxide has diffraction peak intensities at 2θ (diffraction angle) = 23.7 ± 0.5°, 33.6 ± 0.7°, 36.5 ± 0.7° and 56.7 ± 0.5°.
3. A separator for an electrical storage device comprising the pre-doped sheet according to claim 1 or 2.
4. An electricity storage device comprising the pre-doped sheet according to claim 1 or 2.
5. A method for producing a pre-doped sheet for an electricity storage device, comprising:
3. The method for producing a pre-doped sheet according to claim 1, further comprising the step of applying a coating material containing the pre-doping agent and an organic solvent to a surface of a porous sheet substrate.
6. A method for producing a pre-doped sheet for an electricity storage device, comprising:
3. The method for producing a pre-doped sheet according to claim 1, wherein the pre-doping agent is kneaded with a resin and then molded.
7. A method for producing a pre-doped sheet for an electricity storage device, comprising:
3. The method for producing a pre-doped sheet according to claim 1, further comprising coating a surface of a release film substrate with a paint containing the pre-doping agent and an organic solvent.
Citation Information
Patent Citations
Preparation method for positive plate containing Li2MoO3 coating layer
CN107195463A
Positive electrode sheet of lithium ion capacitor, lithium ion capacitor and negative electrode lithium pre-intercalation method thereof
CN110246699A
Train running control system provided with treatment reproduction func tion and computor
JP1977020510A
Nonaqueous electrolyte secondary battery, its separator, and their manufacture
JP1998302839A
Separator for nonaqueous electrolyte secondary battery and nonaqueous electrolyte secondary battery
JP2014170661A